The ecology and evolution of plant-insect interactions among hybrid populations of the invasive plant, tamarisk (Tamarix sp.), in the western United States - Williams, Wyatt I., author; Norton, Andrew, advisor; Friedman, Jonathan, committee member; Hufbauer, Ruth, committee member; Nissen, Scott, committee member; Bauerle, William, committee member (Colorado State University. Libraries, 2012)
Tamarisk is one of the most abundant invasive tree species in the western United States. Several species belonging to the genus Tamarix were imported intentionally to the U.S. in the mid-nineteenth century. Currently, most U.S. populations are comprised of a hybrid swarm between T. ramosissima and T. chinensis and other species. Negative consequences of hybrid tamarisk invasion include alteration of ecosystem functioning and decreases in native biodiversity. Very few natural enemies attack this invasive plant, contributing to its success on the landscape. In an attempt to provide top-down population control, a specialized herbivore that coevolved with tamarisk in its native range was intentionally released in the introduced range (i.e. biological control). I investigated interactions between tamarisk hybrids and herbivores in order to better understand the dynamics that contribute to the control of this exotic weed. In Chapter 1, which was published in Volume 57 of The Southwestern Naturalist, I describe how a native stem-boring beetle was found attacking tamarisk populations in eastern Colorado, western Kansas, and southwest Nebraska. This is an important discovery because very few native insects have been reported to consume this plant and never at the levels of the stem-borer. The beetle may reduce tamarisk growth and fecundity on the Great Plains, providing evidence for the biotic resistance hypothesis. In Chapter 2, I investigate the interaction between drought and herbivory by the biological control agent, Diorhabda carinulata. Under which environmental conditions or geographical locations can biological control be maximized? Finally, in Chapter 3, I speculate whether hybrid tamarisk individuals or populations differ in plant performance and herbivore defense traits. Since the biological control agent coevolved with one parent species, T. ramosissima, I hypothesized that some hybrids may be more or less susceptible to attack by this herbivore. Success of biological control may hinge upon the level of species introgression, and if hybridization occurs predictably across the landscape, managers can exploit this information for tamarisk control. My research not only attempts to improve control strategies, but also addresses fundamental questions in plant-insect ecology and evolution.
Keywords: biotic resistance; limited resource model; introgression; drought stress; hybridization; biological control of weeds